Peran Public Relations (Hubungan Masyarakat) Dalam Meningkatkan Reputasi MAN 1 Banyuwangi - Moh. Harun Al Rosid; M. Syahrul Munir (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The objectives of this study are: (1) to determine the role of public relations in improving the reputation of MAN 1 Banyuwangi and (2) to determine the supporting and inhibiting factors of public relations in improving the reputation of MAN 1 Banyuwangi. This research method uses descriptive qualitative, with data collection techniques through interviews, observation and documentation. Data analysis used interactive 3 models of Miles & Hurberman (1) data reduction, (2) data presentation and (3) conclusion and verification, while the data validity technique used triangulation. The results show that the reputation of MAN 1 Banyuwangi in 2019 has increased. This was realized because the Public Relations staff had worked hard and worked together from all components of the school, such as teachers, employees, and students with stakeholders. The role of Public Relations Staff in improving the reputation of MAN 1 Banyuwangi in 2019 is as follows: (1) Collaborating with community leaders, (2) Conducting harmonious reciprocal relationships with the surrounding community and student guardians, (3) Developing positive opinions of MAN 1 Banyuwangi in the eyes of the community and student guardians, (5) Conducting promotions through brochures, oral and student achievements, (6) Consultation with internal stakeholders regarding policies.